2013
DOI: 10.1603/ec12284
|View full text |Cite
|
Sign up to set email alerts
|

Wide Spread Cross Resistance to Pyrethroids in <I>Aedes aegypti</I> (Diptera: Culicidae) From Veracruz State Mexico

Abstract: Seven F1 strains of Aedes aegypti (L.) were evaluated by bottle bioassay for resistance to the pyrethroids d-phenothrin, permethrin, deltamethrin, λ-cyalothrin, bifenthrin, cypermethrin, α-cypermethrin and z-cypermethrin. The New Orleans strain was used as a susceptible control. Mortality rates after a 1h exposure and following a 24h recovery period were determined. The resistance ratio between the 50% knockdown values (RRKC50) of the F1 and New Orleans strains indicated high levels of knockdown resistance (kd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 25 publications
5
66
0
2
Order By: Relevance
“…The resistance to DDT recorded in all the populations evaluated concurs with the findings of other earlier studies, in which general resistance to this agent was observed [15,29,34,35]. In some of these studies, it was suggested that this resistance came from a population of Ae.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The resistance to DDT recorded in all the populations evaluated concurs with the findings of other earlier studies, in which general resistance to this agent was observed [15,29,34,35]. In some of these studies, it was suggested that this resistance came from a population of Ae.…”
Section: Discussionsupporting
confidence: 90%
“…They would also explain the results obtained in this and other studies carried out in Colombia where there is resistance to pyrethroids such as permethrin and cyfluthrin, even those these have not been used or minimally used in public health [5]. The presence of the I1,016 mutation in Colombia provides the first evidence of another mechanism of resistance to pyrethroids, in addition to the enzymatic alteration previously described in different populations of other regions of Colombia [5,15,29]. We found relatively low I1,016 homozygote frequencies as compared to other pyrethroid resistant populations from other countries [28,[39][40][41][42].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This situation is beneficial for insecticide resistance management; providing critical "islands" of pyrethroid susceptibility that provide a source for susceptibility alleles. Because wide cross resistance to pyrethroids has been reported among mosquito populations across Mexico, 31,32 the use of nonpyrethroid molecules listed in the new Official Mexican policy for the surveillance and control of vectors 6 will help to maintain the sink of pyrethroid-susceptible Ae. aegypti in Yucatan State.…”
Section: Discussionmentioning
confidence: 99%